Aplicación móvil para seguimiento de vacunas y procedimientos con lectura de código QR en la identificación de mascotas (2021)
Health authorities estimate that there are 903,573 dogs in the city of Bogotá and of these 90,000 are strays (Bogotá Council). In addition, Kantar World Panel says in a study carried out in Colombia, that 3,692,365 households have pets and that This amount, 60.3% have dogs, 22.3% cats and 17.4% have both. Finally, the Ministry of Health shared information in which they calculate 794,142 between dogs and cats vaccinated in a single semester in Bogotá. These animals that are part of our family more than pets, it is necessary to carry a document where their vaccinations are monitored.